1987
DOI: 10.1530/acta.0.1150125
|View full text |Cite
|
Sign up to set email alerts
|

The influence of naloxone on exercise-induced increase in plasma pituitary hormones and the subjectively experienced level of exhaustion in healthy males

Abstract: Opioid peptides seem to play a role as modulators of the pituitary function in man. In the present study, the effect of naloxone on exercise-induced pituitary hormone release and the subjectively experienced level of exhaustion were investigated in nine healthy males. A submaximal work test was performed on two occasions using a bicycle ergometer: 10 min on 50% of maximal working capacity (MWC), immediately followed by 10 min on 80% of MWC. Ten min before exercise, each subject received, in a single-blind rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…In normal subjects, the infusion of naloxone elevates plasma ACTH and cortisol but only if given in high doses, above 10 -15 mg (1,3,32,36,39,40). In agreement with these data, we found that the infusion of approximately 9 mg naloxone, over 6 1 ⁄2 h, had no effect on plasma ACTH levels during normocortisolism.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In normal subjects, the infusion of naloxone elevates plasma ACTH and cortisol but only if given in high doses, above 10 -15 mg (1,3,32,36,39,40). In agreement with these data, we found that the infusion of approximately 9 mg naloxone, over 6 1 ⁄2 h, had no effect on plasma ACTH levels during normocortisolism.…”
Section: Discussionsupporting
confidence: 87%
“…The acute administration of opioid peptides may have no effect (8), may inhibit (9), or may increase (2, 10 -13) basal or TRH-stimulated TSH release. Moreover, several studies have found that naloxone, in doses up to 20 mg, had no effect on basal and stimulated TSH secretion (1,5,14,15), whereas other authors have found a decrease in basal TSH secretion (11, 16) or a blunted TSH response to TRH or exogenous opiates (16, 17) in normal subjects.In a recent study (18), we found a dose-dependent inhibitory action of cortisol on TSH secretion in Addison patients (18). Our results suggested a glucocorticoid-mediated suppression of the pituitary sensitivity to TRH, although a synergistic effect at the hypothalamic level could not be excluded.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The project is investigating this arresting puzzle. On the apparent "contradictory" effects on arousal of these two drugs in the biomedical literature, see Julien 1988, Berryhill, Benumof & Janowsky 1979, and Bramnert & Hokfelt 1987 11. There are, however, user groups which have re cently fo rmed to help people avoid "bad" heroin, and several harm reduction programs in New Yo rk City, like the Lower East Side Needle Exchange, regularly post lists of bad heroin which includes information as to what might have been added to the drug to produce the undesired effects.…”
Section: Journal Of Psychoactive Drugs 388mentioning
confidence: 99%
“…Plasma ACTH-cortisol concentrations are known to increase during physical exercise, together with a significant elevation in circulating GH and PRL levels (for review : Howlett 1987). In addition, exercise is accompanied by a rise in the circulating concentrations of endogenous opioids (Howlett 1987), which are thought to exert an inhibitory control on the exercise-induced ACTH increase (Bramnert & Hökfelt 1987). These ob¬ servations prompted us to investigate whether OT was capable of inhibiting the ACTH rise during physical exercise and whether endogenous opioids were involved in the mechanism of action of OT.…”
mentioning
confidence: 99%